Enhancing Digital Literacy in Social Studies through Augmented Reality Media - Rizal Akbar Darmawan; Ade Budi Salira; Yeni Kurniawati; Dina Siti Logayah; Riko Arrasyid (Jurnal Pendidikan Ilmu Sosial, 2024)
Digital literacy is an aspect of education that plays an important role in sharpening the quality of human resources, which lies in the potential and formation of learning experiences. This research has an innovative form of interactive learning in the classroom by presenting augmented reality media as an alternative social studies learning media to increase digital literacy in students to improve students' digital literacy. Augmented reality media can help students learn interactively in digital literacy by creating the impression of 3D objects. The method used is quasi-experimental with a nonequivalent control group design. The results of the data analysis showed that  there were differences in students' digital literacy skills before and after being given augmented reality-based interactive learning media  treatment in experimental classes in social studies learning (0.000 0.05), there were differences in students' digital literacy skills between before and after treatment PopUp Book media in the control class in social studies learning (0.000 0.05)